A NEIL1 single nucleotide polymorphism (rs4462560) predicts the risk of radiation‐induced toxicities in esophageal cancer patients treated with definitive radiotherapy. Issue 23 (10th September 2013) - Chen, Yun; Zhu, Meiling; Zhang, Zhen; Jiang, Guoliang; Fu, Xiaolong; Fan, Min; Sun, Menghong; Wei, Qingyi; Zhao, Kuaile
<x xml:space="preserve">Abstract</x> BACKGROUND To assess the association between single nucleotide polymorphisms (SNPs) of base‐excision repair genes and clinical outcomes, the roles of genetic variants of 3 selected genes—flap structure‐specific endonuclease 1 (FEN1), 8‐hydroxyguanine DNA glycosylase (hOGG1), and nei endonuclease VIII‐like 1 (NEIL1)—were investigated in radiation‐induced esophageal toxicity (RIET), radiation pneumonitis (RP), and overall survival (OS) after radio(chemo)therapy in patients with esophageal squamous cell carcinoma (ESCC). METHODS NEIL1 reference SNP 4462560 (rs4462560) and rs7402844, hOGG1 rs1052133 and rs293795, and FEN1 rs4246215 and rs174538 were genotyped in 187 patients with ESCC who received definitive radiotherapy with or without chemotherapy. Kaplan‐Meier cumulative probabilities and Cox proportional hazards regression models were used to assess the effect of the genotypes on the risk of RIET, RP, and OS. RESULTS The authors observed that patients who had the NEIL1 rs4462560 GC/CC genotype had a statistically significantly lower risk of both grade ≥2 acute radiation‐induced esophageal toxicity (RIET) (adjusted hazard ratio [HR], 0.421; 95% confidence interval [CI], 0.207‐0.856; P = .017) and grade ≥2 acute radiation pneumonitis (RP) (adjusted HR, 0.392; 95% CI, 0.163‐0.946; P = .037) compared with patients who had the GG genotype, but the genotype did not affect OS (adjusted HR, 0.778; 95% CI, 0.471‐1.284; P = .326). There were no significant findings for other the SNPs under investigation. CONCLUSIONS The NEIL1 rs4462560 SNP may serve as a predictor of acute RIET and RP risk but not of OS. Larger prospective studies are needed to validate these findings. Cancer 2013;119:4205–4211. © 2013 American Cancer Society.